Preliminary investigation of 6, 7-dihydropyrazolo[1, 5-a]pyrazin-4-one derivatives as a novel series of mGlu5 receptor positive allosteric modulators with efficacy in preclinical models of schizophrenia. Issue 2 (15th January 2016) - Conde-Ceide, Susana; Alcázar, Jesús; Alonso de Diego, Sergio A.; López, Silvia; Martín-Martín, María Luz; Martínez-Viturro, Carlos M.; Pena, Miguel-Angel; Tong, Han Min; Lavreysen, Hilde; Mackie, Claire; Bridges, Thomas M.; Daniels, J. Scott; et al.
Graphical abstract: Abstract: As part of our efforts to identify a suitable back-up compound to our recently disclosed mGlu5 positive allosteric modulator (PAM) clinical candidate VU0490551/JNJ-46778212, this letter details the investigation and challenges of a novel series of 6, 7-dihydropyrazolo[1, 5- a ]pyrazin-4-one derivatives. From these efforts, compound4k emerged as a potent and selective mGlu5 PAM displaying overall attractive in vitro (pharmacological and ADMET) and PK profiles combined with in vivo efficacy in preclinical models of schizophrenia. However, further advancement of the compound was precluded due to severely limiting CNS-related side-effects confirming the previously reported association between excessive mGlu5 activation and target-related toxicities.